2000
DOI: 10.1034/j.1600-0447.2000.101001073.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of coercive behaviours in psychiatric admissions

Abstract: Legal and clinical efforts to reduce the level of coercive pressures on patients need to recognize the importance of mental-health professionals, including especially those who are not legally mandated to participate in the admission process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
0
21
0
3
Order By: Relevance
“…These insights enabled the treatment team to develop plans that could address and substantially improve Mr. B's deficits in voluntarism and hence in the adequacy of his capacity for informed consent. Here, the assessment of voluntarism was pivotal to the resolution of the case and permitted the patient to assert the self-determination he had always in essence possessed (20). In more difficult and less plastic cases, recognition of deficits in voluntarism may not automatically restore this capacity (21).…”
Section: Discussionmentioning
confidence: 98%
“…These insights enabled the treatment team to develop plans that could address and substantially improve Mr. B's deficits in voluntarism and hence in the adequacy of his capacity for informed consent. Here, the assessment of voluntarism was pivotal to the resolution of the case and permitted the patient to assert the self-determination he had always in essence possessed (20). In more difficult and less plastic cases, recognition of deficits in voluntarism may not automatically restore this capacity (21).…”
Section: Discussionmentioning
confidence: 98%
“…Lidz et al [25] interviewed patients who identified health professionals as the most coercive group at the time of admission to hospital, stating that both verbal and physical coercion were used to pressurize patients into accepting hospitalisation. This is certainly the group exerting most pressure on patients, at least in terms of the therapeutic measures deemed necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Although mental health professionals have worked hard to minimise the negative attitudes towards mental health in the community, 39,40 these negative attitudes remain present even within services, 41 suggesting a need to remain focused on the interactions of all clinicians. The importance of this approach is supported by the work of the MacArthur Foundation who coined the phrase 'procedural justice' 42 to express a similar view. For inpatients, the fact that one in four voluntary patients experience coercion suggests consideration of the consent process for intervention in hospital needs to be reviewed, and implied consent in this patient group may not be sufficient.…”
Section: Implications and Limitationsmentioning
confidence: 96%